ΔNp63 intronic miR-944 is implicated in the ΔNp63-mediated induction of epidermal differentiation - Kim, Kyu-Han (Nucleic Acids Res, 2015)
ΔNp63 is required for both the proliferation and differentiation of keratinocytes, but its role in the differentiation of these cells is poorly understood. The corresponding gene, TP63, harbors the MIR944 sequence within its intron. However, the mechanism of biogenesis and the function of miR-944 are unknown. We found that miR-944 is highly expressed in keratinocytes, in a manner that is concordant with that of ΔNp63 mRNA, but the regulation of miR-944 expression under various conditions did not correspond with that of ΔNp63. Bioinformatics analysis and functional studies demonstrated that MIR944 has its own promoter. We demonstrate here that MIR944 is a target of ΔNp63. Promoter analysis revealed that the activity of the MIR944 promoter was markedly enhanced by the binding of ΔNp63, which was maintained by the supportive action of AP-2 during keratinocyte differentiation. Our results indicated that miR-944 biogenesis is dependent on ΔNp63 protein, even though it is generated from ΔNp63 mRNA-independent transcripts. We also demonstrated that miR-944 induces keratin 1 and keratin 10 expression by inhibiting ERK signaling and upregulating p53 expression. Our findings suggested that miR-944, as an intronic miRNA and a direct target of ΔNp63, contributes to the function of ΔNp63 in the induction of epidermal differentiation.